Buddhism and the dynamics of transculturality: new approaches - Kellner, Birgit (Religion and society, 2019)
For over 2500 years, Buddhism was implicated in processes of cultural interaction that in turn shaped Buddhist doctrines, practices and institutions. While the cultural plurality of Buddhism has often been remarked upon, the transcultural processes that constitute this plurality, and their long-term effects, have scarcely been studied as a topic in their own right. The contributions to this volume present detailed case studies ranging across different time periods, regions and disciplines, and they address methodological challenges as well as theoretical problems. In addition to casting a spotlight on topics as diverse as the role of trade contacts in the early spread of Buddhism, the hybrid nature of religious practices in Japan or Indo-Tibetan relations in Tibetan polemical literature, the individual papers jointly raise the question as to whether there might be something distinct about how Buddhism steers and influences forms of cultural exchange, and is in turn shaped by modalities of cultural interaction throughout Asian, as well as global, history. The volume is intended to demonstrate the need for investigating transcultural dynamics more closely in the study of Buddhism, and to suggest new avenues for Buddhist Studies